The Bible a global history - Gordon, Bruce 1962- (Basic Books, 2024)
"In The Bible, Bruce Gordon tells the astounding story of the Bible's journey around the globe and across more than two thousand years, showing how it has shaped and been shaped by changing beliefs and believers' radically different needs. The Bible has been a tool for violence and oppression, and it has expressed hopes for liberation. God speaks with one voice, but the people who receive it are scattered and divided-found in desert monasteries and Chinese house churches, in Byzantine cathedrals and Guatemalan villages. Breathtakingly global in scope, The Bible tells the story of this sacred book through its many and diverse human encounters, revealing not a static text but a living, dynamic cultural force."
Keywords: Bibel; Geschichte; Bible / History; Bible / Use / History; Histoire; Christianisme; Bible; Bible / Influence / Histoire; Bible / Histoire; history (discipline); Christianity